Computer Music Modeling and Retrieval. Genesis of Meaning in Sound and Music 5th International Symposium, CMMR 2008 Copenhagen, Denmark, May 19-23, 2008 Revised Papers - Ystad, Sl̜vi.; Kronland-Martinet, Richard.; Jensen, Kristoffer. (Lecture Notes in Computer Science, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Symposium on Computer Music Modeling and Retrieval, CMMR 2008 - Genesis of Meaning in Sound and Music, held in Copenhagen, Denmark, in May 2008. The 21 revised full papers presented were specially reviewed and corrected for this proceedings volume. CMMR 2008 seeks to enlarge upon the Sense of Sounds-concept by taking into account the musical structure as a whole. More precisely, the workshop will have as its theme Genesis of Meaning in Sound and Music. The purpose is hereby to establish rigorous research alliances between computer and engineering sciences (information retrieval, programming, acoustics, signal processing) and areas within the humanities (in particular perception, cognition, musicology, philosophy), as well as to globally address the notion of sound meaning and its implications in music, modeling and retrieval.